Micropropagation of Marsdenia brunoniana Wight & Arn. - A Rare Antidiabetic Plant (Plant Tissue Culture and Biotechnology, 2012)
Shoot multiplication of Marsdenia brunoniana was obtained from the nodal explants of mature plants using MS with different concentrations and combinations of growth regulators. Maximum explant response and highest number of shoots per explant was obtained on MS fortified with 1.0 mg/l BAP. The highest degree of shoot profilieration was found to be 90%. The combination of BAP and Kn was also found to be effective for regeneration. The regenerated shoots were successfully rooted on MS supplemented with 0.5 mg/l NAA, after sequential hardening, survival rate was 90%.   Key words: Marsdenia brunoniana, Antidiabetic plant, Micropropagation, Conservation   D. O. I. 10.3329/ptcb.v21i1.9613   Plant Tissue Cult. & Biotech. 21(1): 89-93, 2011 (June) - Short communication